2017
DOI: 10.1016/j.leaqua.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Am I a leader? Examining leader identity development over time

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(174 citation statements)
references
References 67 publications
11
133
1
3
Order By: Relevance
“…Along similar lines, Day and Sin () found that students who reported higher levels of leader identity were rated by their coaches as exhibiting higher levels of leadership within their teams. Miscenko, Guenter, and Day () also observed a positive association between postgraduate students’ identification as leaders and self‐reported leadership skills over the course of a 7‐week leadership training module. Together, these strands of theory and evidence suggest that people who identify as leaders are more likely to be recognized as such.…”
Section: Introductionmentioning
confidence: 90%
“…Along similar lines, Day and Sin () found that students who reported higher levels of leader identity were rated by their coaches as exhibiting higher levels of leadership within their teams. Miscenko, Guenter, and Day () also observed a positive association between postgraduate students’ identification as leaders and self‐reported leadership skills over the course of a 7‐week leadership training module. Together, these strands of theory and evidence suggest that people who identify as leaders are more likely to be recognized as such.…”
Section: Introductionmentioning
confidence: 90%
“…One reason for the failure of formal leadership training is that a leader only develops from formal programming or job/life experience to the extent that he or she is purposefully engaging in an autonomous and self‐regulated growth process—a process defined in the current article as leader self‐development . Although other critical accelerators of leader development include goal‐setting (Johnson, Garrison, Hernez‐Broome, Fleenor, & Steed, ), learning orientation (Dragoni, Tesluk, Russell, & Oh, ), challenging experiences (McCauley, Ruderman, Ohlott, & Morrow, ), experimentation with new identities (Ibarra, ; Miscenko, Guenter, & Day, ), and feedback (DeRue & Wellman, ), the sine qua non is the leader's own internal processes.…”
mentioning
confidence: 99%
“…Miscenko, Guenter, and Day () assert that both skill development and identity development are critical components of leadership development. A leader identity, in particular, is the extent to which individuals think of themselves as a leader (Miscenko et al., ). Drawing on a summary of literature, Hammond, Clapp‐Smith, and Palanski () outline four dimensions of leader identity development.…”
Section: Leader Identitymentioning
confidence: 99%